2018
DOI: 10.1071/rd17255
|View full text |Cite
|
Sign up to set email alerts
|

Systemic adiponectin treatment reverses polycystic ovary syndrome-like features in an animal model

Abstract: The present study examined the efficacy of adiponectin for regulating the reproductive, metabolic and fertility status of mice with polycystic ovary syndrome (PCOS). PCOS was induced in prepubertal (21- to 22-day-old) mice using dehydroepiandrosterone (6mg 100g-1day-1 for 25days), after which mice were administered either a low or high dose of adiponectin (5 or 15µgmL-1, s.c., respectively). PCOS mice exhibited typical features, including the presence of numerous cystic follicles, increased circulating androge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 63 publications
2
17
0
Order By: Relevance
“…Transplantation of BAT from control healthy rats into hyperandrogenic PCOS female rats enhances their BAT activity, increases serum adiponectin levels and ameliorates several key PCOS traits including irregular cycles and insulin resistance (Yuan et al 2016). This study also revealed that exogenous adiponectin administration recapitulated the beneficial effects from BAT transplantation (Yuan et al 2016), which was also confirmed in another hyperandrogenized mouse model of PCOS (Singh et al 2017). Moreover, the findings that transgenic mice that overexpress adiponectin are protected from the induction of androgen excess metabolic PCOS traits, while mice that lack adiponectin display exaggerated or comparable PCOS features to the classic hyperandrogenized PCOS mouse model, highlights that modulation of adipokines, such as adiponectin, may provide a promising novel therapeutic strategy for the management of PCOS (Benrick et al 2017).…”
Section: Current Implications and Future Directions From Basic Researsupporting
confidence: 65%
See 1 more Smart Citation
“…Transplantation of BAT from control healthy rats into hyperandrogenic PCOS female rats enhances their BAT activity, increases serum adiponectin levels and ameliorates several key PCOS traits including irregular cycles and insulin resistance (Yuan et al 2016). This study also revealed that exogenous adiponectin administration recapitulated the beneficial effects from BAT transplantation (Yuan et al 2016), which was also confirmed in another hyperandrogenized mouse model of PCOS (Singh et al 2017). Moreover, the findings that transgenic mice that overexpress adiponectin are protected from the induction of androgen excess metabolic PCOS traits, while mice that lack adiponectin display exaggerated or comparable PCOS features to the classic hyperandrogenized PCOS mouse model, highlights that modulation of adipokines, such as adiponectin, may provide a promising novel therapeutic strategy for the management of PCOS (Benrick et al 2017).…”
Section: Current Implications and Future Directions From Basic Researsupporting
confidence: 65%
“…At present, understanding the precise role the adipokine adiponectin plays in the development of PCOS is of particular interest. Adiponectin is important in glucose and lipid metabolism and has been observed to be decreased in women with PCOS (Manneras-Holm et al 2011) and several PCOS mouse models (Benrick et al 2017, Caldwell et al 2017, Singh et al 2017. Transplantation of BAT from control healthy rats into hyperandrogenic PCOS female rats enhances their BAT activity, increases serum adiponectin levels and ameliorates several key PCOS traits including irregular cycles and insulin resistance (Yuan et al 2016).…”
Section: Current Implications and Future Directions From Basic Researmentioning
confidence: 99%
“…However, the literature regarding TLR expression in patients with PCOS is scarce. Two studies presented data describing increased TLR4 in ovarian tissues from animal models of PCOS [54,55], and it has been reported that ovarian cumulus cells from women with PCOS presented an abnormal TLR expression [56]. Gonzalez et al [57,58] recently reported increased TLR2 expression in peripheral blood mononuclear cells in women with PCOS after ingestion of cream regardless of obesity, and a similar increase in TLR4 expression that occurred mostly in obese women with the syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…After successful modeling, the model group (n = 39, three mice dead, three mice sacri ced) were randomly divided into two groups: maternal-PCOS group (n = 20; 0.9% sodium chloride, s.c.) and maternal-PCOS+APN group (n = 19; APN, 10 mg/kg/day, s.c.) [32]. The control group was recorded as maternal-control group (n = 10, two mice dead, three mice sacri ced; 0.9% sodium chloride, s.c.).…”
Section: Exogenous Apn Treatment In Early Pregnancymentioning
confidence: 99%